Transforming ex-Coal Mining Sites into Sustainable Plantations: A Case Study of Food Natural Sustainability Project in Bomba Group - Waluyo, Ponco; Sastrodiharjo, Istianingsih; Hendayana, Yayan (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The Ministry of Agriculture (Kementan) is encouraging efforts to convert former mining land into productive agricultural areas to increase national food production and stocks amidst the global food crisis. Land Reclamation Technology is a necessity to reduce the cost of reclamation of ex-mining land into agricultural land. The method of reclamation of ex-mining land by moving top soil from another place is not recommended because this is a step to solve the problem by creating other new problems. Sustainability Business Model for such rejuvenation projects refer to Collaboration and Community Based and must be prioritize all stakeholders (all parties involved and affected by the activities carried out by the business) rather than the interests of shareholders.